AlPO4–C composite coating for high emissivity and oxidation protection applications. (June 2013) - Roy, S; Maharana, R; Gokul Laxmi, S; Sakthivel, Y; Roy, M; Bhanu Prasad, V V; Das, D K
Abstract : AlPO4 –C coating deposited by sol–gel technique on Ni base superalloy substrate Nimonic-75 has been examined for high emissivity applications. The coating showed a spectral (2–25 μm wavelength) emissivity in the range of 0·8–0·91, and the emissivity increased with coating thickness. The coating exhibited a reasonably good adhesion with the substrate, as determined from nanoscratch test. The above coating also had a good oxidation resistance in air at 800 and 900°C under cyclic heating and cooling conditions.